Creep Compliance and Relaxation Moduli of PmB 25 A and PmB 45 A Gußasphalts at Different Temperatures - Fettahoglu, Abdullah; Genes, Mehmet Cemal; Kunt, Mehmet Metin (Asce-Amer Soc Civil Engineers, 2018)
PmB 25 A and PmB 45 A Gu ss asphalts (poured asphalts) are commonly used to pave orthotropic steel bridge deck surfaces, especially in Germany, because they are light, stiff, and easily applied. The behavior of asphalt is time- and temperature-dependent, so the stress-strain relationship is represented mathematically using viscoelasticity. Asphalt mixtures are not homogeneous but are composite mixtures, and the tensile and compression components of their stiffness moduli must be determined separately. Here, the time- and temperature-dependent stiffness moduli of PmB 25 A and PmB 45 A Gu ss asphalts are derived using indirect tensile test and a new method to allow the creep compliances and relaxation moduli of PmB 25 A and PmB 45 A Gu ss asphalt types to be determined at 25 and 40 degrees C.
Keywords: Indirect tensile test (IDT); Creep compliance; Relaxation modulus; Gu ss asphalt; Viscoelasticity